Arisan Swarga Santhi Sebagai Implikasi dari Konsep Menyama Braya di Banjar Adat Bebalang Bangli - Wismayani, Sang Ayu Putu; Asli, Luh (Jayapangus Press, 2025)
Humans are social creatures who cannot live alone, humans always live together with other humans in a community group. In social life, there is definitely friction that causes socio-cultural problems. This also happens to the Balinese people in general, and the Bebalang Traditional Banjar community in particular. Phenomenon like a brother Those in the Bebalang Traditional Banjar have experienced shifts along with developments in technology and education. This of course affects activities like a brother. For this reason, in the Bebalang Traditional Banjar a social gathering called Arisan was created Swarga Santi namely a social gathering with the concept of helping families who are experiencing grief. The aim of this research is to find out how social gathering works Swarga Santi it implements the concept like a brother. The method used in this research is a qualitative descriptive method. The process of collecting data in research was carried out through literature study and interviews. The research results show that Arisan Swarga Santi is an activity that plays a role in helping Banjar residents who are experiencing grief. Each Head of Family is charged Rp. 50,000 for every arisan member who dies, with the number of arisan participants Swarga Santi 205, then each member will receive a condolence fund of Rp. 10,250,000. There is Arisan Swarga Santi This really helps members, and is a manifestation of like a brother. Helping families who are experiencing grief because he immediately receives cash so it can be used immediately. On the other hand, it is also easier for other members because they no longer need it damn boss, because it had been replaced with Rp. 50,000 thousand. Apart from that, it is a form like a brother, every member of the social gathering is obliged to help with the procession of the event at the funeral home.